2022
DOI: 10.1021/acs.inorgchem.1c03209
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Octachloro- and Octaazido-Functionalized T8-Cages and Application to Recyclable Palladium Catalyst

Abstract: Unprecedented T8 cages bearing eight chloromethyldimethylsilylethyl substituents were obtained in excellent yield from the readily and commercially available octavinylsilsesquioxane.The chloro groups can be quantitatively substituted by azido ones to yield the corresponding octaazido T8 without rearrangement of the cage. The syntheses of both functionalizable POSSs are scalable (gram-scale). The azido-functionalized T8 compound constitutes a versatile building block able to undergo copper-catalyzed azide-alkyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…S13†) demonstrated the all- cis structure of 5 , with three single peaks attributed to the T-unit silicon atoms (Si in blue) at −78.79 ppm, silicon atoms of carbosilane (Si in green) at 4.86 ppm, and M-unit silicon atoms (Si in red) at 12.08 ppm, which is in accordance with those found in the previous reports. 25,33,34 In addition, the MALDI-TOF mass spectrum confirmed the structure of compound 5 with its ([M + Na] + , 2667.54, calcd 2667.88) peak.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…S13†) demonstrated the all- cis structure of 5 , with three single peaks attributed to the T-unit silicon atoms (Si in blue) at −78.79 ppm, silicon atoms of carbosilane (Si in green) at 4.86 ppm, and M-unit silicon atoms (Si in red) at 12.08 ppm, which is in accordance with those found in the previous reports. 25,33,34 In addition, the MALDI-TOF mass spectrum confirmed the structure of compound 5 with its ([M + Na] + , 2667.54, calcd 2667.88) peak.…”
Section: Resultsmentioning
confidence: 72%
“…Here we describe two new tetrachloro and tetraazido-substituted all-cis-T 4 , prepared following a similar synthetic strategy to that used in our previous work. 33,34 From the tetraazido-substituted compound, a novel all-cis-T 4 bearing BINOL and triazole moieties (Scheme 1A) as well as an innovative 29-8-29membered tricyclic ladder-type compound bearing an all-cis-T 4 core and two organic linker (BINOL and triazole units)-containing hybrid side macrorings (Scheme 1B) were synthesized via copper-catalyzed Huisgen cycloaddition (CuAAC). The fluorescence spectroscopy analysis of these two novel hybrid siloxane-based compounds shows that their capability of binding halides and the ladder-type compound leads to selective recognition of iodide ions.…”
Section: Introductionmentioning
confidence: 99%
“…3 b ,14 Typically, the preparation of azido-functionalized POSSs involves the azidation of chlorides using sodium azide (NaN 3 ) as the nucleophilic reagent, as reported in the synthesis of double-decker cages containing two or four azido groups, as well as T 8 cages with one or multiple terminal azido groups. 12 e ,15 Due to the strong nucleophilicity of N 3 − , cage rearrangement occurs during the azidation of 3-chloropropyl T 8 POSS (T 8 Cl 8 ), resulting in the formation of a mixture of T 8 , T 10 , and T 12 cages with the predominant product being the T 10 cage (∼35% isolated yield) which has been subsequently utilized for synthesizing giant molecules 9 c ,16 and heterogeneous catalysts. 9 d Alternatively, Liu et al reported a straightforward and scalable method (yield > 90%) for synthesizing azido-functionalized T 8 cages by sequential hydrosilylation of octavinyl POSS (T 8 Vi 8 ) with chloromethyldimethylsilane and nucleophilic substitution of the chlorine by NaN 3 .…”
Section: Introductionmentioning
confidence: 99%